The influence of rainfall seasonality and climate change on the demography of Aloe Dichotoma, a long-lived succulent tree from semi-arid southern Africa - Gallaher,Kirsten Sarah Leilani (Percy FitzPatrick Institute of African Ornithology, 2015)
Includes bibliographical references.